Characterization of epitope-blocking ELISA for differential diagnoses of secondary flavivirus infections - Loroño Pino, Maria Alba, author; Beaty, Barry J., advisor (Colorado State University. Libraries, 2008)
West Nile virus (WNV) and Dengue virus (DENY) infections cause significant public health and animal health problems in countries around the world. Accurate laboratory results and diagnoses are essential elements of effective treatment of patients. On a broader scale, accurate diagnoses are critical for public health officials to select appropriate control and prevention measures. However, accurate diagnoses of WNV and DENY infections are currently complicated in areas where multiple flaviviruses circulate. To address this complication, the dissertation project investigated the ability of WNV-specific monoclonal antibodies to compete actively in binding the epitopes on the NS1 peptides and to distinguish between antibodies induced by different flaviviruses. Developing a test distinguish between antibodies to different flaviviruses would significantly improve differential diagnostic capabilities, and reduce false positive WNV diagnoses for humans and horses potentially infected by other flaviviruses. For the diagnosis of WNV infections in humans, an epitope-blocking enzyme-linked immunosorbent assay (b-ELISA) using the WNV-specific monoclonal antibody (MAb) 3.1112G and the flavivirus-specific MAb 6B6C-1 was evaluated. Sera from patients previously diagnosed with WNV infections and with dengue infections were tested. The WNV-specific b-ELISA was efficacious in diagnosing WNV infections in humans with primary infections. The sensitivity and specificity of this test were 90.8% and 91.9%, respectively. However, in tropical regions where people have experienced multiple flavivirus infections, the use of the b-ELISA for WNV diagnosis is contraindicated, due to the 8o% false positive rate using this protocol. Arrays of synthetic peptides of the non-structural-1 (NS1) and the envelope (E) proteins of WNV were also evaluated as diagnostic reagents for peptide-based ELISA for WNV. All WNV peptides investigated accurately diagnosed WNV infections; however, the WNV NS1-1 peptide was found to be the best peptide to distinguish between recent dengue infections and sera classified as negative for flavivirus infections. Finally, b-ELISA was evaluated for its ability to detect antibodies to WNV in 14 horses sequentially infected with WNV and SLEV, SLEV and WNV, or DENY and WNV. The sensitivity and specificity of b-ELISA for detecting antibodies to WNV were 90.9% and 91.7%, respectively in these test results. B-ELISA was specific for detecting antibodies to WNV.
Keywords: dengue virus; epitope-blocking ELISA; flavivirus; synthetic peptides; West Nile virus; virology